Association between cognitive diagnosis and a range of significant life events in an elderly essential tremor cohort: a longitudinal, prospective analysis - Berry, Diane S.; Nguyen, Diep; Cosentino, Stephanie; Louis, Elan D. (Frontiers in Neurology, 2023)
Background: Although essential tremor (ET) patients have greater odds of mild cognitive impairment (MCI) and dementia than age-matched controls, the functional consequences of these enhanced odds are unknown. We examined associations between cognitive diagnosis and the occurrence of near falls, falls, use of a walking aid or a home health aide, non-independent living, or hospitalizations within a prospective, longitudinal study of ET cases. Methods: 131 ET cases (mean baseline age = 76.4 + 9.4 years) completed a battery of neuropsychological tests and questions about life events, and were assigned diagnoses of normal cognition (NC), MCI, or dementia at baseline, and at 18, 36, and 54 month follow-ups. Kruskall-Wallis, Chi-square, and Mantel-Haenszel tests assessed whether diagnosis was associated with the occurrence of these life events. Results: Cases with final diagnoses of dementia more often reported non-independent living than did NC or MCI cases, and more often used walking aids than did NC cases, all p’s <0.05. Cases with a final MCI or dementia diagnosis more often employed a home health aide than did NC cases, all p’s <0.05. Moreover, Mantel-Haenzsel tests revealed linear associations between the occurrence of these outcomes and level of cognitive impairment, p’s <0.001 (i.e., dementia > MCI > NC). Conclusion: Cognitive diagnosis was associated with ET cases’ reported life events, including use of a mobility aid, employment of a home health aide, and removal from an independent living situation. These data provide rare insights into the important role cognitive decline plays in the experiences of ET patients.